2017
DOI: 10.1038/s41598-017-05568-7
|View full text |Cite
|
Sign up to set email alerts
|

Tomatoes protect against development of UV-induced keratinocyte carcinoma via metabolomic alterations

Abstract: Prolonged tomato consumption can mitigate ultraviolet (UV) light induced sunburn via unknown mechanisms. Dietary carotenoids distributed to skin are hypothesized to protect skin against UV-induced damage, although other phytochemicals may play a role. We hypothesize that tomato consumption would protect against skin cancer. SKH-1 hairless and immunocompetent mice (n = 180) were fed AIN-93G or AIN-93G + 10% tangerine or red tomato powder for 35 weeks. From weeks 11–20, mice (n = 120) were exposed to 2240 J/m2 U… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
56
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
3
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 61 publications
(59 citation statements)
references
References 45 publications
(57 reference statements)
2
56
1
Order By: Relevance
“…Accordingly, consumption of tomato paste has been shown, in a randomized controlled study, to protect against acute and long-term photodamage [ 112 ]. In particular, supplementation of tomato paste before UV exposure was able to dampen skin erythema and to reduce mitochondrial DNA damage [ 112 , 113 ]. Moreover, it has been recently showed that, in hairless and immunocompetent mice, tomato consumption was able to protect against the development of UVB-induced keratinocyte carcinoma [ 113 ].…”
Section: Fruits and Vegetables As Powerful Sources Of Antiaging Anmentioning
confidence: 99%
“…Accordingly, consumption of tomato paste has been shown, in a randomized controlled study, to protect against acute and long-term photodamage [ 112 ]. In particular, supplementation of tomato paste before UV exposure was able to dampen skin erythema and to reduce mitochondrial DNA damage [ 112 , 113 ]. Moreover, it has been recently showed that, in hairless and immunocompetent mice, tomato consumption was able to protect against the development of UVB-induced keratinocyte carcinoma [ 113 ].…”
Section: Fruits and Vegetables As Powerful Sources Of Antiaging Anmentioning
confidence: 99%
“…To study tSGAs further, quantitative analysis methods are necessary. In order to maximize the amount of tSGAs detected and separated in our method, we first compiled a target list of biologically relevant tSGAs by surveying the literature (Alseekh et al, 2015; Cichon et al, 2017; Cooperstone et al, 2017; Fujiwara et al, 2004; Hövelmann et al, 2019; Iijima et al, 2009; Zhu et al, 2018). Tomato steroidal glycoalkaloid species were prioritized based on their perceived abundance in the tomato clade, previous structural characterization, and having an established record of being impacted by or a part of biological processes such as ripening or plant defense, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Although these compounds are typically reported as anti-nutritional (Ballester et al, 2016; Cárdenas et al, 2016, 2015; Itkin et al, 2013), other studies suggest a health-promoting role. In fact, emerging evidence suggests that some tSGAs may play a role in positive health outcomes associated with tomato consumption (Cayen, 1971; Choi et al, 2012; Cooperstone et al, 2017; Lee et al, 2004). While these compounds continue to be evaluated both in planta and in vivo , there is a lack of quantitative and validated methods to extract and measure tSGAs from tomatoes; a critical need for additional research in this area.…”
Section: Introductionmentioning
confidence: 99%
“…Tomatoes colour, its weight and taste qualities are very important indices for consumers. It is known, that red coloured tomatoes are better preferred for consumers, but very often in the supermarkets we could find tomatoes with other coloursyellow, orange, brown and black (Cooperstone et al, 2017;Borghesi et al, 2011). Fruit colour is one of the main factors, which determines consumer choice (Breksa et al, 2015;Stommel et al, 2005).…”
Section: Introductionmentioning
confidence: 99%